Petroleum-Degrading Fungal Isolates for the Treatment of Soil Microcosms - Dalel Daâssi; Fatimah Qabil Almaghrabi (Microorganisms, 2023)
The main purpose of this study was to degrade total petroleum hydrocarbons (TPHs) from contaminated soil in batch microcosm reactors. Native soil fungi isolated from the same petroleum-polluted soil and ligninolytic fungal strains were screened and applied in the treatment of soil-contaminated microcosms in aerobic conditions. The bioaugmentation processes were carried out using selected hydrocarbonoclastic fungal strains in mono or co-cultures. Results demonstrated the petroleum-degrading potential of six fungal isolates, namely KBR1 and KBR8 (indigenous) and KBR1-1, KB4, KB2 and LB3 (exogenous). Based on the molecular and phylogenetic analysis, KBR1 and KB8 were identified as Aspergillus niger [MW699896] and tubingensis [MW699895], while KBR1-1, KB4, KB2 and LB3 were affiliated with the genera Syncephalastrum sp. [MZ817958], Paecilomyces formosus [MW699897], Fusarium chlamydosporum [MZ817957] and Coniochaeta sp. [MW699893], respectively. The highest rate of TPH degradation was recorded in soil microcosm treatments (SMT) after 60 days by inoculation with Paecilomyces formosus 97 ± 2.54%, followed by bioaugmentation with the native strain Aspergillus niger (92 ± 1.83%) and then by the fungal consortium (84 ± 2.21%). The statistical analysis of the results showed significant differences.